Sustainable Plastic Management and Circular Economy Strategies in Unilever Indonesia - Yuli Setiyono; Luh Putu Mahyuni (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The increasing volume of plastic waste has intensified environmental challenges globally, particularly in Indonesia, the second-largest contributor to marine plastic pollution. This study aims to analyze the implementation of circular economy principles in a multinational company committed to environmental sustainability, focusing on plastic waste management. A qualitative descriptive case study approach was employed, with data collected through in-depth interviews with sustainability managers, waste bank coordinators, MSMEs, and Environmental Agency officials, complemented by secondary sources including the 2024 Sustainability Report. Findings indicate that Unilever operationalizes circular economy through three key strategies: reduce, reuse, and recycle. The reduce strategy involves eco-friendly packaging innovations; the reuse strategy is implemented via the u-refill station program, promoting refill-based consumption; and the recycle strategy leverages a network of over 4,000 waste banks and advanced recycling technologies like CreaSolv®, managing over 90,000 tons of plastic by 2024. Successful implementation is influenced by economic, technological, social, regulatory, and collaborative factors, while challenges include infrastructure limitations, fluctuating recycled plastic prices, and low public awareness. The study highlights that circular economy is both a technical and social process, requiring multi-stakeholder engagement and systemic policy support to achieve sustainable circularity at scale.